O konieczności badań nad historią nauczania jęz yków obcych - Harbig, Anna Maria (Neofilolog, 2010)
Glottodidactic research is focused on the needs to educate teachers of foreign languages, who perform their job “here and now”. As a result there is little attention paid to the history of teaching foreign languages. In the present article there are arguments for the necessity of a wider introduction of the subject of history into the scope of interest of glottodidactics. An effort is made to show that it is only after further consideration of the didactic tradition that there can be a fuller understanding of the current discussions and developmental tendencies in foreign language instruction. These arguments are preceded by a characterization of the current state of research.